2019
DOI: 10.1111/jpc.14542
|View full text |Cite
|
Sign up to set email alerts
|

Educational intervention does not reduce non‐invasive urine contamination rates in children presenting to the emergency department

Abstract: Aim: Urinary tract infection is common in children with high contamination rates with non-invasive urine sampling (NIU). Our aims were to evaluate an educational tool for decreasing contamination rates and find factors associated with contamination. Methods: This was a prospective cohort interventional study with a review of microbiology data and medical records of all NIU specimens collected at a large tertiary children's emergency department (ED) over a 1-year period. The intervention was the provision of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Contamination rates seem to differ by gender with 10.5% of male samples and 16.4% of female samples being contaminated [25]. Other sources also find contamination is significantly higher in females and in those aged 0-3 months and over 12 years or if the urine sample is collected at home [4,33].…”
Section: Clean Catch Urinementioning
confidence: 98%
See 1 more Smart Citation
“…Contamination rates seem to differ by gender with 10.5% of male samples and 16.4% of female samples being contaminated [25]. Other sources also find contamination is significantly higher in females and in those aged 0-3 months and over 12 years or if the urine sample is collected at home [4,33].…”
Section: Clean Catch Urinementioning
confidence: 98%
“…Interventional studies have shown that a staff education package highlighting the importance of cleaning did not change contamination rates in an emergency department but as monthly clinical activity increased, so did the likelihood of contamination, suggesting it is an avoidable occurrence [33]. A randomised trial of cleaning with soap vs. not cleaning in 350 patients found significantly lower contamination rates in the cleaning group (7.8%) vs. the non-cleaning group (23.9%) [38].…”
Section: Perineal Cleaningmentioning
confidence: 99%
“…2 Similarly, Jacob et al attributed their findings to decreased staff time to describe the ideal collection process and to delays in sending specimens to the laboratory. 1 While these factors may have played a role in the present data, the inconsistencies in results between UCCs #1 and #5 suggest that some variable(s) may moderate the relationships between patient volume and contamination rate. Perhaps the effect decreases for institutions in which providers receive more training in the MSUC collection technique.…”
Section: Dear Editor Urine Culture Contamination Rates As a Functionmentioning
confidence: 65%
“…We read with great interest the recent 1-year study on urine contamination in an emergency department. 1 We were particularly interested in the finding that higher monthly patient volume predicted contamination as this has not been previously reported in the literature. The interpretability of this result was hindered because it was a single-institution study.…”
Section: Dear Editor Urine Culture Contamination Rates As a Functionmentioning
confidence: 98%
“…Literature reviews show patient and staff education of a clean catch urine culture collection technique alone is not always effective at consistently reducing urine culture contamination. 8,9,10 The intervention team hypothesized that an effective multifactorial method to reduce urine culture contamination would be a combination of staff education on appropriate midstream and straight catheter collection techniques, verbal and visual education for patients, and staff and physician identification of patients who would provide more accurate urine cultures via straight catheterization than clean catch.…”
Section: Specific Aimsmentioning
confidence: 99%